Novel sustainable composites prepared from cork residues and biopolymers (Biomass and Bioenergy)
Novel low-density biocomposites based on cork and two biodegradable matrices, poly(lactic acid) and poly(caprolactone), were prepared by simple melting-mixing. The surface acylation of cork was studied as a strategy to increase the compatibility with the matrices. The obtained composites were characterized in terms of thermal and mechanical properties, morphology, density and water absorption behavior. All composites showed a good dispersion of cork and a strong interfacial adhesion between the cork particles and the polymeric matrices as evidenced by SEM. The Young's modulus values of the composites were little affected for cork loads up to 10%; but for higher loadings, a considerable decrease on this parameter was observed resulting in more flexible materials. These sustainable cork based materials could find applications in several domains such as in flooring and structural applications, depending on the amount of cork and the polymeric matrix used.

Rigid polyurethane foams derived from cork liquefied at atmospheric pressure (Polymer International, 2014)
The aim of this study was to evaluate the possibility of using polyols derived from liquefied cork in the production of novel bio-based polyurethane foams (PUFs). For that purpose, different liquefaction conditions were used at atmospheric pressure and moderate temperature where poly(ethylene glycol) and glycerol were used as solvents and sulfuric acid as catalyst. The ensuing polyols were used to produce foams which were characterized using structural, morphological, thermal and mechanical analyses to demonstrate that liquefaction conditions play a crucial role in the properties of the foams. The resulting foams exhibited the typical cellular structure of PUFs with low densities (57.4–70.7 kg m−3) and low thermal conductivities (0.038–0.040 W m−1 K−1). However, the mechanical properties differed significantly depending on the liquefaction conditions. The best stress–strain results were obtained for PUFs prepared using the polyol with lowest IOH and water content (Young's modulus of 475.0 kPa, compressive stress (σ10%) of 34.6 kPa and toughness of 7397.1 J m−3). This PUF was thermally stable up to 200 °C and presented a glass transition temperature of around 27 °C. The results obtained demonstrate that these polyols from liquefied cork yield PUFs that are adequate materials for insulation applications. © 2014 Society of Chemical Industry

Isolation of suberin from birch outer bark and cork using ionic liquids: A new source of macromonomers (Industrial Crops and Products, 2012)
Cholinium hexanoate, a biocompatible and biodegradable ionic liquid, was recently demonstrated to efﬁciently and selectively extract suberin domains from cork, combining high extraction efﬁciency with isolation of a partial depolymerised material. In the present paper, we report a comparative study of the characterisation of suberin extracted from birch outer bark and from cork using cholinium hexanoate. It became apparent that both extracted suberin samples showed still a cross-linked nature, i.e. likely to be closely related to in situ suberin. Suberin samples were mainly constituted by oligomeric or polymeric structures in turn essentially composed by long chain hydroxyacids monomers. Their high thermal stability together with the oligomeric/polymeric nature, open new perspectives for suberin use as macromonomers in the development of bio-based polymeric materials. This also contributes for the valorisation of suberin rich agro-forest residues.